2017
DOI: 10.13004/kjnt.2017.13.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Results between Soft Ruptured Disc and Foraminal Stenosis Patients in Posterior Cervical Laminoforaminotomy

Abstract: ObjectivePosterior cervical laminoforaminotomy is used to relieve cervical nerve root compression caused by a laterally herniated soft cervical disc or spondylotic spur and its several advantages and disadvantages compared with anterior cervical discectomy were reported. We compared surgical results between soft ruptured disc and foraminal stenosis in posterior cervical laminoforaminotomy.MethodsWe performed a retrospective review of 47 patients performed single level posterior cervical laminoforaminotomy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…In a study by Henderson (19). In our study also, we found that 93.75% of patients with soft disc were found to have excellent and good results, and in patients with foraminal stenosis, this rate remained at 75%.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a study by Henderson (19). In our study also, we found that 93.75% of patients with soft disc were found to have excellent and good results, and in patients with foraminal stenosis, this rate remained at 75%.…”
Section: Discussionsupporting
confidence: 77%
“…However, it was found that with 50% and more of facetectomies highly likely caused instability (4,5). In the study of Yoo et al, 31.2% of facetectomies was sufficient for the removal of the soft disc, whereas in patients with foraminal stenosis, 48.8% of facetectomies were found to have lower clinical results (19). In our study, the facetectomy rate was 32% in patients with soft disc hernias and 42% in patients with foraminal stenosis.…”
Section: Discussionmentioning
confidence: 44%
“…ree studies documented good/excellent postoperative outcomes with limited reports of adverse events following open CLF [Table 1]. [13][14][15] Yilmaz (2016) et al found that performing 83 open CLF to address posterolateral soft discs or foraminal stenosis resulted in 66 excellent and 13 good outcomes (Odom's Criteria); additionally, 79 (95%) showed improvement in postoperative radicular complaints, with just two adverse events (i.e., AE: 1 dural tear, and one wrong level surgery) [Table 1]. [13] Further pros for CLF included; better operative exposure to limit perioperative neural injuries, a shortened LOS, and greater preservation of stability (i.e., avoidance of fusion 1].…”
Section: Good/excellent Postoperative Outcomes With Limited Adverse E...mentioning
confidence: 99%
“…(2017) evaluated the overall outcomes for 27 patients undergoing open CLF for soft disc herniations vs. 20 for lateral/foraminal stenosis, they found both groups exhibited 92.6% excellent and 7.4% good outcomes (Odom’s Criteria), with better results recorded for those with soft discs [ Table 1 ]. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation